PROPERTIES OF LAMINATED PARALEL PANELS AS AN ALTERNATIVE TO SOLID WOOD - Ferraz, Joana Mendes (2015)
Laminated strand lumber and oriented strand lumber (LSL/OSL) are structural composite lumber, which has been recently introduced in the building construction market, as an alternative to solid wood utilization. This research aimed to analyze the technical feasibility of producing LSL and OSL. Additionally, was also investigated the effect of using different lengths of particles on physical and mechanical properties of the composites and comparing it to Chrysophyllum sp solid wood. Six wood panels were produced, utilizing particles of 15 and 30 centimeters of length, divided into two analyses (OSL/LSL), with three repetitions in each one. The following tests were performed: static bending (MOE//, MOR//) non-destructive testing (MOEd//), parallel compression strength (COMP//); thickness swelling (TS), water absorption (AA) and linear expansion (EL) for 2 and 24 hours. These tests were conducted according to the ASTM D 5456 (ASTM, 2006).  It was not identified the effect of particle length on mechanical properties. On the other hand, the composite produced with shorter particles (OSL) presented better dimensional stability than the LSL, produced with longer ones. Flexural properties and compression strength of OSL/LSL composites presented values close, but still lower, than those observed for solid wood.